Du Nil au Rhin. L’imaginaire égyptien du médecin de Bingen - Valérie Martini (Histoire, Médecine et Santé, 2016)
In the Roman necropolis of Bingen-Am-Rhein, a the military town in the center of Germany, a set of 67 medical instruments was found in a tomb in 1860. A small bronze statuette of a hippopotamus with an erected cobra, probably made in Egypt, was placed in a bronze basin. The two emblematic animals of the Egyptian bestiary witness the impact of the idealized image of Egypt on Roman medicine. For the Romans, the hippopotamus represents the prosperity and the benefits brought by the Nile flood, a water with healing qualities. It is also an animal with a medical intelligence, able to heal itself by practicing bleeding. The cobra, uraeus, refers to the goddess Isis, whose cult spread throughout the Roman provinces with the expansion of the Empire.